Practice of code of ethics and accuracy in reporting by print media criminal court reporters - Musalayah, Mageswari (2013)
The practice of code of ethics among the media practitioners is still unclear. There is a gap in the studies over the meaning of the practice of code of ethics. Commitment to truth and accuracy in news reporting is recognized as a fundamental obligation of journalistic ethics. For journalists in Malaysia, they have their own Canons of Journalism (COJ) since 1989 (Shivadas & Krishnamoorthy, 2004) but there is no watchdog to oversee that such code of conduct of news media is strictly adhered to by the journalists (Kamarul Ariffin, 1996). COJ was chosen as the basis for the study on the criminal court reporters’ understanding on the practice of code of ethics in their daily work. The focus of the study is to explore whether accuracy, which is listed as the primary responsibility to be observed by the Malaysian journalists, is being subscribed as a core value by them. The study was conducted at the Kuala Lumpur Court Complex in Jalan Duta and Palace of Justice in Putrajaya. On the research design, the study used qualitative and phenomenology approach as its data collection method. The study used qualitative methods to obtain its data namely in-depth interview, observation and field notes. The reporters were interviewed until the data reaches to the saturation point. This has caused 12 reporters from the English and Malay newspapers to be purposively chosen for this research. Two senior news editors have also been interviewed to strengthen the findings of the study. The researcher conducted data collection, data management and data analysis concurrently. The researcher has used NVivo 7 software to manage and analyze the data. Thematic analysis and constant comparison were used to sort and analyze the data to get organized findings. The researcher conducted member check, peer debriefing and be a good listener to ensure validity of the study. An audit trail was adopted to ensure its reliability. Triangulation was also helpful to ensure internal validity, reliability and trustworthiness of the study. The data was also checked on the applicability of certain ethical principles of the Kant’s Duty Ethics Theory and Brockett’s The Dimensions of Ethical Practice Model thus contributing to its usage in the area of journalism. Among others, the findings of this study confirmed to Kant’s theory that it is the good will of the court reporters to practice code of ethics regardless of consequences and that reason demands them to act rationally by adopting accuracy in reporting news daily. In addition, this study supports the Brockett’s model, among others, to have a strong foundation of personal value system and priority to be accurate in reporting. The findings revealed that although majority of the criminal court reporters have various understanding on the practice of code of ethics in their line of duty, it all confirmed that ethics is more to do with guidelines or principles concerning the rights and wrongs of human conduct. However, the reporters’ understanding on the practice of code of ethics is at “elementary” level. The status of practice of all the elements of code of ethics among them is at “formative stage”. It is not a well-formed culture yet. The level of thinking on code of ethics which formed journalism values was still unclear. On the other hand, accuracy is considered as core value in the code of ethics of print media court reporters. The findings revealed that diversity is also a matter of accuracy. The reporters applied various ethical ways to co-operate among themselves in order to uphold accuracy in reporting court news. Most of them said that retaining accuracy did not affect the execution of their duties daily as they accept it as part of their job and responsibility.